2017
DOI: 10.1128/msphere.00446-17
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Universal System for Gene Manipulation in Aspergillus fumigatus: In Vitro -Assembled Cas9-Guide RNA Ribonucleoproteins Coupled with Microhomology Repair Templates

Abstract: Tackling the multifactorial nature of virulence and antifungal drug resistance in A. fumigatus requires the mechanistic interrogation of a multitude of genes, sometimes across multiple genetic backgrounds. Classical fungal gene replacement systems can be laborious and time-consuming and, in wild-type isolates, are impeded by low rates of homologous recombination. Our simple and universal CRISPR-Cas9 system for gene manipulation generates efficient gene targeting across different genetic backgrounds of A. fumig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
230
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(233 citation statements)
references
References 59 publications
3
230
0
Order By: Relevance
“…Introduction of Cas9-sgRNA RNPs with or without a donor template yielded hundreds to thousands of edited B. cinerea transformants. So far, similar approaches have been rather rarely used for CRISPR/Cas genome editing in fungi [2224]. An advantage of the use of RNP over endogenous Cas9 and sgRNA expression is the reduced probability of potential off-target mutagenic activities of Cas9, because of its limited stability in cells [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction of Cas9-sgRNA RNPs with or without a donor template yielded hundreds to thousands of edited B. cinerea transformants. So far, similar approaches have been rather rarely used for CRISPR/Cas genome editing in fungi [2224]. An advantage of the use of RNP over endogenous Cas9 and sgRNA expression is the reduced probability of potential off-target mutagenic activities of Cas9, because of its limited stability in cells [52].…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of sgRNA can be achieved either via plasmids or by in vitro synthesized sgRNA. More recently, transformation with Cas9-sgRNA ribonucleoprotein (RNP) complexes has been successfully applied in selected fungi [2224].…”
Section: Introductionmentioning
confidence: 99%
“…As one means of minimizing off-target effects, directly transfected Cas9 protein reduces the off-target cleavage rate when compared with Cas9 expression by a plasmid or mRNA transfection in mammalian cells (16). One recent study has demonstrated that direct delivery of Cas9–gRNA ribonucleoprotein can facilitate genome editing in A. fumigatus (10). Based on these improvements, we produced a simple, efficient, and accurate site-directed mutagenesis system to investigate structure–phenotype relationships of the azole target Cyp51A.…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair via homology-directed repair requires a homologous DNA template with sequence similarity to the adjacent region of the DSB locus, whereas NHEJ ligates the DSB, leading to indels in a template-independent manner. The Cas9/CRISPR system has also been successfully applied to A. fumigatus (1012).…”
Section: Introductionmentioning
confidence: 99%
“…Complementation of each RasGEF deletion was achieved by targeted, ectopic integration of each gene under the control of the endogenous promoter using a previously described CRISPR/Cas9 technique (Al Abdallah, Ge, & Fortwendel, ). Briefly, to generate the repair templates for complementation, the coding region plus 1 kb of native promoter for each RasGEF was PCR amplified from genomic DNA and fused to a phleomycin resistance cassette, previously amplified from the plasmid pAGRP (Fortwendel et al, ), using an overlap‐extension PCR technique (Szewczyk et al, ).…”
Section: Methodsmentioning
confidence: 99%